Nutrients in the litter in Eucalyptus saligna Smith stand in São Grabriel, RS - Santos, Joel Carvalho dos; Schumacher, Mauro Valdir; Witschoreck, Rudi; Araújo, Elias Frank de; Lopes, Vicente Guilherme (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
The aim of this work was quantify the stock of nutrients in litter in Eucalyptus saligna Smith stand at 4 and 5 years of age in the municipality of São Gabriel - RS. All material collected at the end of each season, was sent to the laboratory for determination of macronutrients. Total litter for the years 2011 and 2012 was 12.76 and 12.00 Mg ha-1, respectively. The amounts of N, P, K, Ca, Mg and S stored in the litter were 94.4; 4.8; 21.8; 138.8; 25.6 and 8.8 kg ha-1 respectively. The litter is an excellent source of organic matter and nutrient reserves for future rotations.